Time for reorientation in Lomé III? - H. Eisold; R. Hasse (Intereconomics, 1984)
The Lomé Convention with its 63 signatory states in Africa, the Caribbean and the Pacific (ACP) represents the centre-piece of the EC's development policy. The current agreement, Lomé II, expires on February 28, 1985, and negotiations on Lomé III already began in Luxembourg on October 6, 1983. The time has therefore come to take stock and to appraise the possible negotiating positions and areas of conflict facing the partners contracting to Lomé III.
Keywords: 330; ACP-EC Trade